HUBUNGAN ANTARA JUMLAH SIMPANAN DENGAN SISA HASIL USAHA (SHU) PADA ANGGOTA KPRI “JAYA ABADI” KECAMATAN MEJAYAN KABUPATEN MADIUN TAHUN 2011/2012 - Setyo Gilang Dika Rimadana (Universitas PGRI Madiun, 2013)
The purpose of this study were (1) To determine the amount of deposits in member KPRI “J AYA ABADI” Sub Mejayan Madiun district, (2) To determine the SHU (windfall profits) to the members of KPRI “JAYA ABADI” Sub Mejayan Madiun district, and (3 ) To determine the relationship between the amount of deposits to the SHU on KPRI members’ JAYA ABADI “. District Mejayan Madiun district. This research h takes an object on KPRI “Jaya Abadi” Mejayan Kabupten Madiun district with a population of as many as 274 people. Because the population is pretty much the study using a sample of 73 people. The data was collected by observation, wawanacara and documentation. While the analysis tools used to answer the hypothesis is the correlation method. Based on the analysis of data can be seen the magnitude of correlation (r) is 0.3685 which is a positive correlation, ie, if the number of Member Savings (X) increases proportionally the amount of Business (Y) is also increasing. And vice versa, if the number of Member Savings (X) decreases proportionally the number of Business (Y) will also decrease. It is made clear that in order to increase the number of Business, KPRI “JAYA ABADI” Sub Mejayan Madiun district should seek to increase the number of Member Savings. By knowing the correlation coefficient (r) of 0.3685 means hypothesis (Ha) is proposed in this study can be accounted for, ie “There is a significant relationship between the Member Savings Business Profits KPRI” JAYA ABADI “Mejayan Madiun district. This can be proved by using rtabel with dk = 73-2 = 71 is 0.235, while the test criteria is if rhitung> rtabel then Ho is rejected and accept Ha and if rhitung <rtabel the Ha Ho accepted and rejected.